Analisis Pengaruh Debt To Equity Ratio, Return On Investment, Dan Earning Per Share Terhadap Return Saham (Studi Kasus Pada Perusahaan Mining And Mining Service Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2014) - Setyorini, Eko Agustina; , Sri Murwanti, S.E., M.M (2015)
This research aims to know influence of Debt to Equity Ratio (DER), Return On Investment (ROI), and Earning Per Share (EPS) for stock return partially and simultaneously. The examples of this research are 14 Mining and Mining Service companies listed on The Indonesia Stock Exchange in 2012-2014 with as many as 42. The total data used in this research are 14 data. Sampling technique of this study by using purposive sampling method, where the sample was taken according to criteria that determined. The data is taken from ICMD of BEJ Muhammadiyah University of Surakarta. Analysis technique of this research is multiple linear regression, while classic assumption test consist of normality test, multicolinearity test, autocorrelation test, and test heteroskedasitas used to assess the validity of regression equation. Beside that, there are t test, F test on significant level 5% and the coefficient of determination. The result of this studies are t test contain variable of Debt to Equity Ratio (DER) give no effect for stock return, Return On Investment (ROI) give no effect for stock return, Earning Per Share (EPS) give for stock return. The result of F test is variable of Debt to Equity Ratio (DER), Return On Investment (ROI), and Earning Per Share (EPS) give affects for stock return.